Generalized balanced tournament designs with block size four - Chee, Yeow Meng (2014)
In this paper, we remove the outstanding values m for which the existence of a GBTD(4;m) has not been decided previously. This leads to a complete solution to the existence problem regarding GBTD(4;m)s.